Screws, 100° countersunk normal head, offset cruciform recess, close tolerance normal shank, short thread, in alloy steel, cadmium plated. Classification: 1100 MPa (at ambient temperature)/235°C. (15th February 1997) - British Standards Institution,
No abstract available